D’un dualisme bien utile - Vinciane Despret (Revue d'anthropologie des connaissances)
What makes the difference between professionals and amateurs is closely related to the double theme of affect and relations. A way of designing the objectivity in some experimental practices, relies on this contrast: the nature of remplacability of beings under scrutiny is supported by the substitutability of those who put them under scrutiny; this double interchangeability being also grounded on the eradication of personal relationships. A good experimenter is an anonymous “anybody” able to bring to existence another anonymous “anybody”. This is the principle that has been governing science during the last two centuries. However it is not surprising to discover that the scientific sphere has taken for granted one of the essential dimensions which is the landmark of emotions in our culture: the separation between domestic or private space and public space, a separation that is reproduced between scientific and lay practices. The private space is the place of affects and personal relationships – relationships between singular persons; the public space is characterized by the complete substitutability of beings granted rationality and logos and in particular those in the scope of this article: the experimenters. However if we consider the relationships between scientists and “others”, we cannot but notice that other dimensions of affects are involved in these contrasting interplays and play the role of means for differentiation. We will draw on a series of reflections on psychology, anthropology, or primatology, whose recent evolutions contribute to shade a new light on the question of amateurs and affect.